2021
DOI: 10.3390/ijerph19010403
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Bedtime in the PURE Poland Cohort Study and the Link with Noncommunicable Diseases

Abstract: (1) Background: The objective was to investigate the association between sleep duration, bedtime, and noncommunicable diseases in the PURE Poland cohort study. (2) Methods: The baseline study was conducted in 2007–2010. The study group comprised 2023 adult inhabitants of urban and rural areas in Lower Silesia, Poland. The study protocol included questionnaires, blood pressure measurements, blood draws, and anthropometric measurements. Sleep duration and bedtime were self-reported. (3) Results: The median sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…This could explain why children who used screens late at night had more difficulty waking up (76.6%) (Table 3). Consistent to a study conducted by Jakobsson et al [31], more than 30% of the study participants had wake-up difficulty. Many of the children who took part in the study had bedtime delays and sleep disturbances.…”
Section: Wake Up Difficultysupporting
confidence: 89%
See 1 more Smart Citation
“…This could explain why children who used screens late at night had more difficulty waking up (76.6%) (Table 3). Consistent to a study conducted by Jakobsson et al [31], more than 30% of the study participants had wake-up difficulty. Many of the children who took part in the study had bedtime delays and sleep disturbances.…”
Section: Wake Up Difficultysupporting
confidence: 89%
“…Furthermore, in the study, 95.9% of early sleepers had lesser sick days with respiratory illnesses (< 15 days in a year) than 66.8% of the late sleepers (P<0.05). A study conducted in 2022 by Katarzyna et al [19] found that the relative risk of respiratory diseases was two-fold higher in those who went to bed after midnight versus those who went to bed between 10 PM and 12 AM. Hence, late sleepers (>10 PM) increases the risk of respiratory illnesses as proven in our study as well the other studies.…”
Section: Bedtime and Respiratory Illnessesmentioning
confidence: 99%
“…The main research directions in the analyses of the data collected in the Polish PURE cohort during the longterm follow-up period focused on dietary factors [8][9][10][11][12][13][14][15][16], the effect of CETP and PLTP protein activity on lipid disorders [17,18], overweight and obesity [19][20][21][22], atti- tudes toward tobacco smoking [23][24][25][26], alcohol consumption [27], sleep [28], quality of life [29], prevalence and determinants of hypertension [30,31], and carbohydrate metabolism disorders [32][33][34][35][36].…”
Section: Impact Of the Studymentioning
confidence: 99%